2000
DOI: 10.1016/s0925-4439(00)00040-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in Alzheimer’s disease

Abstract: Oxidative balance is emerging as an important issue in understanding the pathogenesis of Alzheimer's disease. Examination of Alzheimer's disease brain has demonstrated a great deal of oxidative damage, associated with both hallmark pathologies (senile plaques and neurofibrillary tangles) as well as in normal appearing pyramidal neurons. While this suggests that oxidative stress is a proximal event in Alzheimer's disease pathogenesis, the mechanisms by which redox balance is altered in the disease remains elusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
413
0
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 733 publications
(430 citation statements)
references
References 48 publications
10
413
0
7
Order By: Relevance
“…When OE was added into already digested A␤ samples with trypsin ( Similarly, ESI-MS analysis of the A␤-OE Glu-C digest yielded signals corresponding to the expected A␤ fragments [4 -11], [12][13][14][15][16][17][18][19][20][21][22], and [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] following cleavage at the carboxy-terminus of glutamic acid (E) residues (Table 2), and the noncovalent complexes between OE and the [4 -11] and [12][13][14][15][16][17][18][19][20][21][22] A␤ Glu-C fragments ( Figure 3). Interactions between OE and the partially cleaved peptide fragments [4 -40] and (Table 4) When OE was added into already digested A␤ samples with Glu-C (Table 4), ESI signals corresponded to ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When OE was added into already digested A␤ samples with trypsin ( Similarly, ESI-MS analysis of the A␤-OE Glu-C digest yielded signals corresponding to the expected A␤ fragments [4 -11], [12][13][14][15][16][17][18][19][20][21][22], and [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] following cleavage at the carboxy-terminus of glutamic acid (E) residues (Table 2), and the noncovalent complexes between OE and the [4 -11] and [12][13][14][15][16][17][18][19][20][21][22] A␤ Glu-C fragments ( Figure 3). Interactions between OE and the partially cleaved peptide fragments [4 -40] and (Table 4) When OE was added into already digested A␤ samples with Glu-C (Table 4), ESI signals corresponded to ...…”
Section: Resultsmentioning
confidence: 99%
“…Free radical reactions and oxidative stress [28,29], as well as unregulated immune response [30,31], are believed to be key factors for the pathogenesis of AD, whereas recent reports suggested a link between heart disease, hypercholesterolemia, and…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is also reported to play a role in the process of AD, as strongly proposed by Smith and Perry [89,90] , and antioxidants may be associated with a lower risk of AD [91] . These treatment strategies for AD are still under way and more investigations and trials are needed to test their efficacy in its prevention or treatment.…”
Section: Other Therapeutic Approaches To Admentioning
confidence: 71%
“…Barthel et al, using positron emission tomography (PET) images of florbetaben (an 18 F-labeled Aβ-targeted PET tracer), demonstrated that nine of ten mildmoderate probable AD participants (DSM-IV and NINCDS-ADRDA criteria) were Aβ-positive, compared to only one of ten healthy controls [49] . Furthermore, in a global phase 2, open-label, non-randomized, multi-center study recruiting a total of 81 men and women with probable mild-to-moderate AD and 69 cognitively unimpaired healthy volunteers aged 55 years and older, florbetaben scans indicated a sensitivity of 80% (95% CI 71-89) and a specificity of 91% (84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98) for discriminating participants with AD from healthy controls [50] .…”
Section: Aβ As a Promising Target For Ad Treatmentmentioning
confidence: 99%